2022
DOI: 10.1002/ijc.34015
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus in relation to colorectal tumor molecular subtypes: A pooled analysis of more than 9000 cases

Abstract: Diabetes is an established risk factor for colorectal cancer. However, colorectal cancer is a heterogeneous disease and it is not well understood whether diabetes is more strongly associated with some tumor molecular subtypes than others. A better understanding of the association between diabetes and colorectal cancer according to molecular subtypes could provide important insights into the biology of this association. We used data on lifestyle and clinical characteristics from the Colorectal Cancer Family Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…BRAF mutations, found in 8-12% of CRC cases, are usually associated with a poor prognosis. They tend to occur in proximal CC, in older patients, and often co-occur with high-level microsatellite instability [21]. Harlid et al (2022), in a pooled analysis including 9,756 CRC patients, confirmed that diabetes particularly increases the risk of BRAF-mutated tumors [21].…”
Section: Discussionmentioning
confidence: 84%
“…BRAF mutations, found in 8-12% of CRC cases, are usually associated with a poor prognosis. They tend to occur in proximal CC, in older patients, and often co-occur with high-level microsatellite instability [21]. Harlid et al (2022), in a pooled analysis including 9,756 CRC patients, confirmed that diabetes particularly increases the risk of BRAF-mutated tumors [21].…”
Section: Discussionmentioning
confidence: 84%